ARTIFICIAL INSEMINATION IN GOAT: A NEW PROSPECT FOR SCIENTIFIC GOAT BREEDING - Dhara, Souvik; Thakur, Swati; Anwar, S.M.S.; Gupta, M.D.; Sinha, S. (Animal Reproduction Update, 2023)
In India major portion of goat farming is extensive and breeding system follows uncontrolled natural mating. For better breeding management there should be sufficient good quality stud bucks. But it is very unfortunate that due to lack of breeding buck more than 30% estrus does remain without service. In order to check the negative selection and for proper management of breeding policy, cryopreservation of superior native buck semen and artificial insemination is the only way. Artificial insemination (AI) is a part of assisted reproductive technology (ART) providing augmentation of genetic make-up in individuals. Artificial insemination in sheep and goat was first described detail in 1987. Globally 0.5 million AIs are performed annually in case of goat which is very less than other animals. Research in the area of cryopreservation of goat semen and artificial insemination has been limited to few research institutes and AI is least practiced in field condition. Intra-cervical insemination is widely practiced in case of does with successful results.